2001
DOI: 10.51481/amc.v43i2.52
|View full text |Cite
|
Sign up to set email alerts
|

Lesiones vasculares abdominales: El desafío del cirujano de trauma

Abstract: Introducción: Las lesiones vasculares abdominales presentan los mayores índices de mortalidad y morbilidad de entre todas las lesiones que puede sufrir un enfermo traumático.Método: Revisión de la clínica, diagnóstico, vías de abordaje y tratamiento de los pacientes con lesiones vasculares intraabdominales, basada en la experiencia en el manejo de 302 enfermos.Resultados: Las heridas penetrantes abdominales constituyen entre el 90%-95% de las lesiones que afectana los vasos abadominales. La lesión abdominal mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Heuer et al 18 reported 10,530 (1.5% of emergency department admissions) cases of abdominal trauma patients with severe vascular injuries in 218 hospitals, over a period of 16 years in Germany; in this case, the difference could be due to the number of hospitals included and the time dedicated to the study. In our country, a comparative reference of a trauma center is Mexico City's Mexican Red Cross Trauma Center itself: in a retrospective study between 2015 and 2017 19 , 42,909 admissions to the emergency department were reported, 1.4% with gunshot wound diagnosis, out of 3 estimated that abdominal vascular injuries are associated with a mean of two to four additional injuries; in our study, we observed that 100% of patients had associated abdominal injuries, with an average of 4.1; an amount similar to the upper limit reported in the referred article. Asensio et al 3 also reported that multiple vascular injury is common; however, we found that 83.3% of patients had injury to a single vessel.…”
Section: Abdominal Vascular Trauma Medical Relevancementioning
confidence: 99%
See 2 more Smart Citations
“…Heuer et al 18 reported 10,530 (1.5% of emergency department admissions) cases of abdominal trauma patients with severe vascular injuries in 218 hospitals, over a period of 16 years in Germany; in this case, the difference could be due to the number of hospitals included and the time dedicated to the study. In our country, a comparative reference of a trauma center is Mexico City's Mexican Red Cross Trauma Center itself: in a retrospective study between 2015 and 2017 19 , 42,909 admissions to the emergency department were reported, 1.4% with gunshot wound diagnosis, out of 3 estimated that abdominal vascular injuries are associated with a mean of two to four additional injuries; in our study, we observed that 100% of patients had associated abdominal injuries, with an average of 4.1; an amount similar to the upper limit reported in the referred article. Asensio et al 3 also reported that multiple vascular injury is common; however, we found that 83.3% of patients had injury to a single vessel.…”
Section: Abdominal Vascular Trauma Medical Relevancementioning
confidence: 99%
“…In our country, a comparative reference of a trauma center is Mexico City's Mexican Red Cross Trauma Center itself: in a retrospective study between 2015 and 2017 19 , 42,909 admissions to the emergency department were reported, 1.4% with gunshot wound diagnosis, out of 3 estimated that abdominal vascular injuries are associated with a mean of two to four additional injuries; in our study, we observed that 100% of patients had associated abdominal injuries, with an average of 4.1; an amount similar to the upper limit reported in the referred article. Asensio et al 3 also reported that multiple vascular injury is common; however, we found that 83.3% of patients had injury to a single vessel. Evidently, the relevance of additional injuries lies not only in the overall increase in the severity index of the wound but also in the complexity and duration of the required treatment, as well as in the risk for developing complications 6,8,20,21 .…”
Section: Abdominal Vascular Trauma Medical Relevancementioning
confidence: 99%
See 1 more Smart Citation